Effects of stocking density on the growth performance, bacterial load and antioxidant response systems of noble scallop Chlamys nobilis. Issue 92 (September 2019) - Liu, Hongxing; Ye, Ting; Soon, Tan Kar; Zhang, Hongkuan; Cheng, Dewei; Li, Shengkang; Ma, Hongyu; Zheng, Huaiping
Abstract: Stocking density is a crucial factor in shellfish aquaculture that affects overall growth performance and health status. Present study analyzes the effects of stocking densities on growth, survival and hemolymph immune status of noble scallop Chlamys nobilis . The scallops with the same size were separately placed in the lantern cages (10 layers per cage) using high stocking density (500 scallops per cage) and low stocking density (100 scallops per cage) and cultivated in the same location for 60 days. The results indicated that the scallops cultivated at high stocking density had significantly higher mortality and slower growth than those cultivated at low stocking density. Moreover, the hemolymph of scallops cultivated at high density showed significantly higher bacterial load, higher reactive oxygen species (ROS), higher expression level of Nrf2 and lower expression level of Keap1, as well as lower antibacterial ability of Vibrio parahemolyticus than that of scallops cultivated at low density. The present results demonstrated that long-term overcrowding is detrimental for the scallops, which can not only lead to high mortality and slow growth, but also cause more vulnerable to pathogenic bacteria. Therefore, we speculated that high stocking density culture practice of scallops in China might be the root of infectious bacteria outbreaks. Highlights: High stocking density decreased scallop survival and growth performance. High stocking density increased bacterial load and ROS level in noble scallop. Increased stocking densities regulated expression levels of antioxidant defense related genes. Elevation of stocking densities decreased antibacterial activity of scallops' hemolymph.